Prevention and rehabilitation of low back pain in nursing workers: an integrative literature review - Zulamar Aguiar Cargnin; Dulcinéia Ghizoni Schneider; Mara Ambrosina de Oliveira Vargas (Universidade Federal de Santa Maria, 2020)
Objective: to identify strategies for the prevention and rehabilitation of low back pain in nursing workers. Method: integrative literature review. The searches took place in the LILACS, MEDLINE / PUBMED, and SCIELO databases, including articles in English, Spanish and Portuguese from 2009 to 2019. Results: the 14 publications found enabled the construction of three categories: "testing strategies", "complementary rehabilitation strategies", and "combined strategies". Prevention consisted mainly of online education and strategies based on the Health Belief Model. The complementary strategies found were massage, myofascial release and yoga. Combined strategies such as the Spine School seem to provide a more adequate model for the management of non-specific lower back pain. Conclusion: because of the small number of publications on the subject, new studies are needed to obtain better results on these strategies usage rates and the adoption of mainly multimodal new approaches for this specific population in its work environment.